Evaluating land use/cover change associations with urban surface temperature via machine learning and spatial modeling: Past trends and future simulations in Dera Ghazi Khan, Pakistan - Mehmood, Muhammad Sajid; Rehman, Adnanul; Sajjad, Muhammad; Song, Jinxi; Zafar, Zeeshan; Shiyan, Zhai; Yaochen, Qin (Frontiers in Ecology and Evolution, 2023)
While urbanization puts lots of pressure on green areas, the transition of green-to-grey surfaces under land use land cover (LULC) change is directly related to increased land surface temperature (LST) — compromising livability and comfort in cities due to the heat island effect. In this context, we evaluate historical and future associations between LULC and LST in Dera Ghazi Khan—one of the top cities in Pakistan—using Landsat TM/OLI data over two decades (2002-2022). After assessing current LULC changes and future predictions, their impact on LST is measured using spatial indices. The future prediction scenarios (2032) for both, LULC and LST, are depicted via Multi-Layer Perceptron-Markov Chain and Artificial Neural Network. While the produced LULC maps show very high accuracy (> 90%), it is expected that due to LULC changes by 2032, ~60% of urban and peri-urban areas will experience very hot to hot temperatures (> 31.5 ◦C). The green-grey conversion in the last two decades (8.7%) and prospect along the main corridors show the gravity of unplanned urban growth at the cost of vegetation and agricultural land (-6.8%). The LST and UHI effect shows a strong positive correlation between urbanization and vegetation removal. The simulation results presented in this study confirm that by 2032, the city will face a 5◦ C high mean temperature based on historical patterns, which could potentially lead to more challenges associated with UHI if no appropriate measures are taken. Our results provide baseline information to urban managers and planners to understand the increasing trends of LST in response to LULC changes. The study is important for urban resource management, sustainable development policies, and actions to mitigate the heat island effect.